INTEGRATED EDUCATION IN PRIMARY SCHOOL MATHEMATICS (Conference Zone, 2022)
In that article talk about of intergration education in elementary school of mathematics. In our time it is necessary know plently of expriense work in phase of integration study in the modern of school, ordinarile issue revitalization of knowledge students. In this article give information about of lesson from mathematics in elementary school.